Comparative study of nitroglycerin dermal patch versus nifedipine in the management of preterm labour - Kaur, Manjeet; Goel, Bharti; Singh, Jasveer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of present study was to compare the effect of nitroglycerin dermal patch and nifedipine for taking control of preterm labor (tocolysis) and to find the safer drug for mother and foetus. Methods: Women with signs and symptoms of preterm labor between gestational ages 26-37 weeks were studied. These women were divided into 2 groups. Group A-50 women were prescribed nitroglycerin dermal patch and in Group B-50 women were given nifedipine. Primary outcome of the study was to delay the delivery for at least 48 hours. Secondary outcomes were gestational age at the time of delivery, prolongation of labor, effect on neonate and adverse effects. Results: Both groups were comparable regarding cervical effacement in cm and gestational age in weeks at the time of enrollment. Gestational age at the time of delivery in weeks (p < 0.01), prolongation of pregnancy in days (p > 0.05), neonatal Apgar score at 5 minutes (p < 0.05), neonatal weight in kg (p < 0.05) and foetal outcomes were better in nifedipine group in comparison to nitroglycerin. The overall side effects were less in nifedipine group as compared to nitroglycerin group. Overall success rate was 88% with nifedipine and 76% in nitroglycerin cases. Conclusions: Both the drugs were able to postpone the delivery for 48 hours. Nifedipine was found to be superior to nitroglycerin dermal patch in prolongation of gestational age at the time of delivery, in perinatal outcome and maternal acceptance.